PSYCHOLOGICAL AND PEDAGOGICAL BASIS OF PROFESSIONAL TRAINING OF FUTURE FINE ARTS TEACHERS - Ikromov Muhammad Anaskhan Hakimjon son (American Journals, 2023)
In the article, the psychological-pedagogical foundations of professional training of future visual arts teachers are highlighted, the methods of implementing integrative relations between them based on the use of active teaching methods are considered.
Keywords: pedagogical education, profession, professional competence, professional excellence, professional skill.